2020
DOI: 10.3390/ijms21134673
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Albumin in the Presence of AGuIX Nanoagents: Structure Stabilisation without Direct Interaction

Abstract: The gadolinium-based nanoagent named AGuIX® is a unique radiosensitizer and contrast agent which improves the performance of radiotherapy and medical imaging. Currently tested in clinical trials, AGuIX® is administrated to patients via intravenous injection. The presence of nanoparticles in the blood stream may induce harmful effects due to undesired interactions with blood components. Thus, there is an emerging need to understand the impact of these nanoagents when meeting blood proteins. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 86 publications
2
11
0
Order By: Relevance
“…Interestingly, the absence of size decrease may indicate that dissolution of the particle, if any, did not occur within a short time period (<15 min). These results also support the fact that serum proteins did not interact with the USNP, as already assumed from synchrotron radiation circular dichroism on mixtures of AGuIX and HSA …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, the absence of size decrease may indicate that dissolution of the particle, if any, did not occur within a short time period (<15 min). These results also support the fact that serum proteins did not interact with the USNP, as already assumed from synchrotron radiation circular dichroism on mixtures of AGuIX and HSA …”
Section: Resultssupporting
confidence: 88%
“…These results also support the fact that serum proteins did not interact with the USNP, as already assumed from Synchrotron radiation circular dichroism on mixtures of AGuIX® and HSA. 30 Most importantly, this analytical procedure was demonstrated to be successfully applied for hydrodynamic radius determination in various complex media, where the classical DLS and TDA-UV lack specificity (see SI, Figures S7 and S8). Hence, the use of a ICP-MS detector coupled to TDA opens new perspectives since it could be easily extended not only to other classes of metallic and hybrid USNPs to determine their behavior in biological media, but also to large biomolecules, such as specifically labelled antibodies.…”
Section: Icp-msmentioning
confidence: 99%
“…At tinc=0, the hydrodynamic size of the AGuIX UNSPs is similar in both types of media, illustrating their colloidal stability. Moreover, an absence of interactions with proteins in serum was noticed, as already reported in others papers [27,38,39]. Soon after dilution, a process of biodegradation occurs as asserted by the USNP size decrease.…”
Section: Assessing Different Populations Sizes and Polydispersity Ind...supporting
confidence: 72%
“…One of the limitations of the study is the use of an aqueous medium that cannot completely mimic the more complex interactions that may arrive in a biological medium but a precedent biodegradation study performed in phosphate buffer and serum has shown a very similar electrophoretic profile for the molecular fragments in both media [ 19 ]. Moreover, AGuIX presents very limited interactions with proteins, such as human serum albumin [ 24 ], confirmed by their very fast renal elimination [ 15 , 16 ]. Altogether, these results indicate that the fragments identified in this study will certainly also be representative of the biological medium.…”
Section: Resultsmentioning
confidence: 99%